1985
DOI: 10.1029/ja090ia09p08173
|View full text |Cite
|
Sign up to set email alerts
|

Coronal mass ejections: 1979–1981

Abstract: In an examination of the Solwind coronagraph images obtained during the interval March 28, 1979, to December 31, 1981, we have identified 998 coronal mass ejections and recorded their structural classes, central latitudes, latitudinal spans, speeds, excess brightnesses, and relative importances. A statistical analysis revealed the following general results. (1) The properties of coronal mass ejections (CMEs) depended strongly on their structure. Curved front, halo, and complex CMEs were the most energetic, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
306
1
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(333 citation statements)
references
References 37 publications
17
306
1
9
Order By: Relevance
“…As seen from coronagraph images, streamers are the most prominent quasi-steady structures in the corona and CMEs often closely interact with streamers as they propagate outward or expand laterally (e.g., Chen et al 2010;Feng et al 2011). Statistical analyses have indicated that many CMEs originate from the streamer belt (e.g., Howard et al 1985;Hundhausen 1993;Eselevich & Tong 1997;Zhao & Webb 2003). Furthermore, recent works have shown that type II radio bursts, which are good observational manifestations of energetic electrons accelerated at shocks, reflect the interaction between shocks and streamers (e.g., Reiner et al 2003;Mancuso & Raymond 2004;Cho et al 2008;Feng et al 2012Feng et al , 2013Kong et al 2012Kong et al , 2015Chen et al 2014) or the shock passing through high-density coronal loops (e.g., Pohjolainen et al 2008;Cho et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As seen from coronagraph images, streamers are the most prominent quasi-steady structures in the corona and CMEs often closely interact with streamers as they propagate outward or expand laterally (e.g., Chen et al 2010;Feng et al 2011). Statistical analyses have indicated that many CMEs originate from the streamer belt (e.g., Howard et al 1985;Hundhausen 1993;Eselevich & Tong 1997;Zhao & Webb 2003). Furthermore, recent works have shown that type II radio bursts, which are good observational manifestations of energetic electrons accelerated at shocks, reflect the interaction between shocks and streamers (e.g., Reiner et al 2003;Mancuso & Raymond 2004;Cho et al 2008;Feng et al 2012Feng et al , 2013Kong et al 2012Kong et al , 2015Chen et al 2014) or the shock passing through high-density coronal loops (e.g., Pohjolainen et al 2008;Cho et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This led to a dominant paradigm of the "loop transient". It is interesting to note that the analogous results for the first 3 years of the Solwind instrument (Howard et al, 1985) found that 2% of CMEs qualified as loops. However, the vast majority of their major events were categorised as "curved fronts" (40%), which are effectively loops without a trailing edge, so the pictures were perhaps not too inconsistent.…”
Section: Morphologymentioning
confidence: 69%
“…It expands and is expelled by magnetic forces in CMEs. The front speeds could exceed up to 3000 kms -1 [61][62][63]. This phenomenon can exhibit a variety of forms, some having the classical "three-part" structure [64].…”
Section: Coronal Mass Ejections (Cmes)mentioning
confidence: 99%
“…Previous study also focused on the properties of CMEs such as occurrence rates, kinetic energy, the locations relative to the solar disk, angular widths, speeds and accelerations, masses, and energies [32,50,[72][73][74][75][76][77][78]. There have been many studies on the statistical properties of CMEs by [63,71,73,77,[79][80][81][82] which based on the SOHO / LASCO observations. The probable conservation of the magnetic support of the former prominence is the physical key factor for the later identification of in-situ observed magnetic clouds in the solar wind with the preexisting CMEs and before existing prominences on the disc.…”
Section: Coronal Mass Ejections (Cmes)mentioning
confidence: 99%